Climbing the mountain : my search for meaning - Douglas, Kirk, 1916- (New York : Simon & Schuster, 1997)
The actor recounts how, after a helicopter crash and a stroke, he returned to his Jewish roots, and found new meaning in his life and reconciliation with his son
Includes index.
Keywords: Douglas, Kirk, -- 1916-; Motion picture actors and actresses -- United States -- Biography; Jewish actors -- United States -- Biography; Actors -- United States -- Biography